Augmented Visual Feedback: Cure or Distraction?. (November 2021) - Eisma, Yke Bauke; Borst, Clark; Paassen, René van; Winter, Joost de
Objective: The aim of the study was to investigate the effect of augmented feedback on participants' workload, performance, and distribution of visual attention. Background: An important question in human–machine interface design is whether the operator should be provided with direct solutions. We focused on the solution space diagram (SSD), a type of augmented feedback that shows directly whether two aircraft are on conflicting trajectories. Method: One group of novices ( n = 13) completed conflict detection tasks with SSD, whereas a second group ( n = 11) performed the same tasks without SSD. Eye-tracking was used to measure visual attention distribution. Results: The mean self-reported task difficulty was substantially lower for the SSD group compared to the No-SSD group. The SSD group had a better conflict detection rate than the No-SSD group, whereas false-positive rates were equivalent. High false-positive rates for some scenarios were attributed to participants who misunderstood the SSD. Compared to the No-SSD group, the SSD group spent a large proportion of their time looking at the SSD aircraft while looking less at other areas of interest. Conclusion: Augmented feedback makes the task subjectively easier but has side effects related to visual tunneling and misunderstanding. Application: Caution should be exercised when human operators are expected to reproduce task solutions that are provided by augmented visual feedback.